The Influence of Regional Original Revenue, General Allocation Fund, Special Allocation Fund on Capital Expenditure in Districts in South Sulawesi Province - Misalayuk, Anthon; Tanggisalu, Jannati; Ampauleng, Ampauleng (Jurnal Pemerintahan dan Politik Lokal, 2025)
Fiscal decentralization is a form of regional autonomy in the aspect of regional financial management. To assist local governments in improving services to the community, the central government provides TKD funds including DAU and DAK which are sources of regional income other than PAD. With this transfer, the local government is expected to maximize its revenue to optimize community services, one of which is through the fulfillment of capital expenditure. This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) on Capital Expenditure in Cities and Regencies in South Sulawesi Province. The research method used is a quantitative method. The population of this research are 24 regencies and cities in South Sulawesi Province with APBD and TKD data from 2022 to 2024 it was 72 and all of them become samples (saturated samples). The analysis method used in this research is multiple regression analysis and supported by EViuws 13 application. The results shows that Regional Real Income and Special Allocation Funds have a positive and significant effect on capital expenditure. Meanwhile, the General Allocation Fund does no effect on Capital Expenditure. The determination coefficient (R²) value for Y is 0.806, it means that 80.60% of the Capital Expenditure Budget can be explained by the three independent variables of the Influence of Regional Real Income, General Allocation Fund, and Special Allocation Fund. Meanwhile, the rest 19.40% can be explained by another factor.